Islam, Cultural Differences, and Intercultural Communication - Taqiyuddin, Muhammad; Mohammed, Samih Salah (Cultural Conflict and Integration, 2025)
This paper explores the intricate relationship between Islam, cultural diversity, and intercultural communication in the context of an increasingly globalized world. Islam, practiced by over 1.9 billion people worldwide, is not a monolithic culture but a religion deeply embedded in a variety of cultural settings across different regions, including Southeast Asia, the Middle East, Africa, and Europe. These cultural differences influence the interpretation and practice of Islamic teachings, leading to diverse expressions of faith that reflect local customs, traditions, and social norms. Such diversity presents unique challenges in intercultural communication, both within Muslim communities and in interactions between Muslims and non-Muslims. Misunderstandings often stem from cultural stereotypes, linguistic differences, and varying communication styles, which can be exacerbated by media portrayals and limited religious literacy. This study emphasizes the importance of cultural humility, empathy, and active listening as essential strategies for effective intercultural dialogue. It also highlights how Islamic values of justice, compassion, and mutual respect provide a strong ethical foundation for promoting peaceful coexistence and intercultural understanding. By examining these dynamics, the paper aims to foster awareness about the significance of recognizing cultural differences within Islam and improving communication across cultural and religious boundaries. This awareness is particularly relevant in multicultural societies, workplaces, and global diplomatic contexts, where it supports social cohesion, reduces prejudice, and enhances collaborative efforts. Ultimately, the research underscores that appreciating the interplay between religion and culture is vital for navigating diversity and building bridges in a pluralistic world.